2008
DOI: 10.1111/j.1532-5415.2008.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Triage Risk Stratification Tool to Identify Older Persons at Risk for Hospital Admission and Returning to the Emergency Department

Abstract: The TRST demonstrated only moderate predictive ability, and ideally, a better prediction rule should be sought. Future studies to develop better prediction rules should compare their performance with that of existing prediction rules, including the TRST and Identifying Seniors at Risk tool, and assess the effect of any new prediction rule on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…Several studies reported composite outcomes of various combinations of undesired outcomes as "any adverse outcome." 66,67,70,76,77,79 The ISAR studies assessed the instrument's prognostic accuracy for ED return visits at 30 to 180 days, functional decline at 30 to 90 days, and hospital readmission at 30 to 180 days. In addition, multiple studies reported composite outcomes of "any adverse outcome" at 30 to 180 days, although the components of the combined endpoint varied from study to study.…”
Section: Screening Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported composite outcomes of various combinations of undesired outcomes as "any adverse outcome." 66,67,70,76,77,79 The ISAR studies assessed the instrument's prognostic accuracy for ED return visits at 30 to 180 days, functional decline at 30 to 90 days, and hospital readmission at 30 to 180 days. In addition, multiple studies reported composite outcomes of "any adverse outcome" at 30 to 180 days, although the components of the combined endpoint varied from study to study.…”
Section: Screening Instrumentsmentioning
confidence: 99%
“…One study reported the prognostic accuracy of TRST for functional decline with the outcome 78 Additionally, five studies assessed a composite outcome of "any adverse outcome" at 30 days using various combinations of endpoints. 10,67,70,77,79 Two studies evaluated "any adverse outcome" at 90 days 65,66 and another two at 120 days. 77,79 Several studies reported prognostic accuracy estimates at various thresholds ranging from one to three "yes" responses on the TRST.…”
Section: Screening Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-rater reliability -kappa 0.94-1.0 (24) / 0.9 (28) Validated by Moons et al (35) Lee et al (36) Ruciman et al (25) VEQ (Vulnerable Elderly Questionnaire)…”
Section: Two Urban Academic Ed N=647mentioning
confidence: 99%
“…Receiver Operating Curve (ROC) of the final PERIL prediction rule, paramedic clinical judgment, and the ISAR tool were also reported and areas under the curve (AUC) were compared. 34 …”
Section: Cjem Jcmumentioning
confidence: 99%